(untitled) (Research, Society and Development, 2019)
In order to contribute to the reflection on the link between evaluation and education, the main purpose of this study is to identify the contributions of the evaluation to the teaching-learning process. The method used to carry out this work was the bibliographical research in papers that discuss the concept of evaluation and its complexities in the current configuration of Brazilian education. Regarding the evaluation theme, it is noticed that there is an evaluation that values measuring, weighing, and testing the students’ knowledge in a traditional way, daily in schools. It was concluded, through this the analysis in light of what the authors had pointed out that it is urgent to make a change in this type of evaluation that still occurs in schools. The evaluation needs to be seen as an instrument where the teacher recognizes and understands the level of learning in which the student is, and from this, formulate the conscious and effective actions in the teaching-learning process; thus, school evaluation is a challenge that requires changes by all those involved in this process.